Impaired glycemia increases disease progression in mild cognitive impairment - Morris, Jill K.; Vidoni, Eric D.; Honea, Robyn A.; Burns, Jeffrey M. (Neurobiology of aging, 2014)
Insulin resistance and type 2 diabetes are associated with cognitive decline and increased risk for Alzheimer's disease (AD). Relatively few studies have assessed the impact of metabolic dysfunction on conversion to AD in mild cognitive impairment (MCI), and it is unclear whether glycemic status is associated with clinically relevant measures of cognitive decline and brain structure in MCI. This study used the Alzheimer's Disease Neuroimaging Initiative database to examine the relationship of baseline glycemia with conversion to AD and longitudinal clinical, cognitive, and imaging measures of decline. Subjects with MCI (n = 264) with baseline and 2-year Clinical Dementia Rating data available were classified according to American Diabetes Association criteria for fasting glucose at baseline. The groups were normoglycemic (fasting glucose, <100 mg/dL; n = 167) or impaired glycemia (fasting glucose, ≥100 mg/dL, n = 97). The impaired glycemia group included individuals with fasting glucose that either reached the American Diabetes Association cut point for impaired fasting glucose or individuals with diagnosed diabetes. Two-year change in Clinical Dementia Rating-Sum of Boxes, cognitive performance testing (global cognition), brain volume (whole-brain and hippocampal volume), fluorodeoxyglucose-positron emission tomography, and conversion to AD were assessed. Subjects with normoglycemia at baseline had less functional (Clinical Dementia Rating-Sum of Boxes) and global cognitive decline over 2 years than subjects with impaired glycemia. Subjects with normoglycemia also lost less whole-brain volume and exhibited lower conversion from MCI to AD. There was no difference in hippocampal volume change or fluorodeoxyglucose-positron emission tomography between groups. These results suggest that baseline glycemia is related to cognitive decline and progression to AD.